Neutrophil-lymphocyte ratio kinetics in patients with advanced solid tumours on phase I trials of PD-1/PD-L1 inhibitors. (January 2018) - Ameratunga, Malaka; Chénard-Poirier, Maxime; Moreno Candilejo, Irene; Pedregal, Manuel; Lui, Andrew; Dolling, David; Aversa, Caterina; Ingles Garces, Alvaro; Ang, Joo Ern; Banerji, Udai; Kaye, Stan; Gan, Hui; et al.
Abstract: Background: Although the neutrophil-lymphocyte ratio (NLR) is prognostic in many oncological settings, its significance in the immunotherapy era is unknown. Mechanistically, PD-1/PD-L1 inhibitors may alter NLR. We sought to characterise NLR kinetics in patients with advanced solid tumours treated with PD-1/PD-L1 inhibitors. Methods: Electronic records of patients treated with PD-1/PD-L1 inhibitors on phase I trials across three sites were reviewed. A high NLR (hNLR) was predefined as >5. Univariate logistic regression models were used for toxicity, response analyses and Cox models for overall survival (OS) and progression-free survival analyses. Landmark analyses were performed (cycle two, three). Longitudinal analysis of NLR was performed utilising a mixed effect regression model. Results: The median OS for patients with hNLR was 8.5 months and 19.4 for patients with low NLR, (hazard ratio [HR] = 1.85, 95% confidence interval [CI] 1.15–2.96, p = 0.01). On landmark analysis, hNLR was significantly associated with inferior OS at all time points with a similar magnitude of effect over time (p < 0.05). On multivariate analysis, NLR was associated with OS (HR 1.06, 95% CI 1.01–1.11, p = 0.01). NLR did not correlate with increased immune toxicity. Longitudinally, NLR correlated with response: NLR decreased by 0.09 (95% CI: −0.15 to −0.02; p = 0.01) per month in responders compared with non-responders. Conclusions: hNLR at baseline and during treatment is adversely prognostic in patients with advanced malignancies receiving PD-1/PD-L1 blockade. Importantly, NLR reduced over time in responders to immunotherapy. Taken together, these data suggest that baseline and longitudinal NLR may have utility as a unique biomarker to aid clinical decision-making in patients receiving immunotherapy. Highlights: High neutrophil-lymphocyte ratio (NLR) at baseline and during treatment is adversely prognostic in patients receiving PD-1/PD-L1 blockade. NLR does not correlate with risk of immune toxicity. NLR decreases over time in responders to immunotherapy.